SYSTEM CONTROL DAN MONITORING SUHU PADA SUB DISTRIBUTION PANEL (SDP) BERBASIS IoT MENGGUNAKAN SENSOR DHT22 UNTUK MENGURANGI TERJADINYA OVERHEAT PADA PT.XYZ - Mulyani, Bambang Adi; Saputra, Bintang Rizky (University of Muhammadiyah Tangerang, 2022)
In carrying out maintenance and repair activities in an industry, of course a level of efficiency and accuracy is needed so that production results are in accordance with the targets set by the company. To fulfil the needs of electricity consumption in a company, a distribution panel is needed as a channel for voltage from the substation to the distribution panel and then distributed back to the production machines. From findings in the field that often occur, the temperature in the panel room has increased and exceeds the temperature thresholds that should be 32̊C, and must not exeed 40̊C (Isnainny, Azharro 2021). Referring to the background above, the author took the initiative to make a control device and monitor temperature and voltage as well as current in a distribution panel. In the modern era and the development of technology, especially in companies and in an education, it is very reasonable to use IoT (Internet of things) based technology so that it can make it easier for users to be able to operate it remote, therefore the author wants to make this control and monitoring system operable long distance. This aims to increase the efficiency of maintenance and repair of work equipment that supports the increase in production results that have been determined by the company. In making the tool the author uses several sensors to read the temperature values contained at that location. The sensors used are the DHT22 sensor as a room temperature value reader, the ZTMP101B sensor as a voltage value reader to be monitored, the SCT-013 sensor is used as an electric current value reader. The author also uses the Blynk application as a place to monitor all value readings generated by the sensor. The author uses the ESP32 microcontroller as the brain in a series of devices. In addition to the integrated wifi module, that becomes a wireless microcontroller is also equipped with quite a lot of GPIO pins, making it easier for the author to utilize the sensors that will be connected to the microcontroller.